DETERMINANT FACTORS AFFECTING THE INCIDENCE OF PLACENTA ACCRETA - hakim, novita dwihastuti; Dwi Izzati; Ernawati (UNIVERSITAS AIRLANGGA, 2024)
Background: Placenta accreta is a rare condition during pregnancy characterized by abnormal placentation that can increase maternal morbidity and mortality. The increase in the incidence of placenta accreta is directly related to the increase in section caesarean rates. The maternal mortality rate in NTB in 2021 was 15% due to hemorrhage, in 2022 there was an increase in the incidence of placenta accreta at the NTB Provincial Hospital. The aim of the research is to identify the determinant factors affecting the incidence of placenta accreta at the NTB Provincial Hospital in 2022. Methods: This was a descriptive observational study. The population in this study were all mothers who delivered at the NTB Provincial Hospital from January to December 2022. The sample number was 50 patients diagnosed with placenta accreta. The sampling technique used was total sampling with the research variable of maternal characteristics. Data were collected from the medical records of mothers with placenta accreta from January to December 2022, and the results were analyzed using descriptive analysis. Results: Placenta accreta patients were more common in mothers with age ≤ 35 years with a median of 34.34 ± 4.28, multiparous parity (76%), overweight BMI (54%), 3-9 years labour spacing (82%), history of SC ˂ 2 times (52%) and ≥ 2 times (48%), and with a history of uterine surgery 24%. Conclusion: Determinant factors that affect the incidence of placenta accreta in NTB Provincial Hospital in 2022 are mothers with age < 35 years, multigravida, overweight body mass index, mostly with a parity of 3-9 years, without degenerative diseases, all have a history of cesarean section and almost a quarter have a history of other operations on the uterus.